2015
DOI: 10.1111/wrr.12344
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive device readouts validated by immunohistochemical analysis enable objective quantitative assessment of acute wound healing in human skin

Abstract: Objective evaluation of cutaneous wounds through use of noninvasive devices has important implications for diagnosis, monitoring treatment efficacy, progression and may lead to development of improved theranostic treatment strategies. However, there is a lack of validation in the use of certain devices in wound repair, where objective measurements taken by noninvasive devices have been corroborated by immunohistochemical analysis. Thus, data from three acute wound-healing studies in healthy volunteers using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 62 publications
(110 reference statements)
0
21
0
Order By: Relevance
“…These wounds are useful from an experimental perspective in that their size and depth can be precisely controlled. As they involve all the components of the healing process, they provide an excellent research tool and have been used to investigate angiogenesis, wound contraction, and wound closure . Numerous studies have been conducted evaluating various treatments for both wounds and scars using a sequential skin punch biopsy model to assess various characteristics and correlated by clinical measurements .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These wounds are useful from an experimental perspective in that their size and depth can be precisely controlled. As they involve all the components of the healing process, they provide an excellent research tool and have been used to investigate angiogenesis, wound contraction, and wound closure . Numerous studies have been conducted evaluating various treatments for both wounds and scars using a sequential skin punch biopsy model to assess various characteristics and correlated by clinical measurements .…”
Section: Resultsmentioning
confidence: 99%
“…Ex vivo models enable immediate and short‐term evaluation of a particular effect on cells and its surrounding tissue components compared with in vivo models that provide direct analysis in the live human subject before, during and after exposure to a stimulus . Human in vivo models are useful as the pathology and physiology of healing is identical to that found in the patient . Both patient and volunteer models have their advantages and limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Moor full‐field laser perfusion imager (Moor FLPI‐2) (Moor Instruments Ltd, Axminster, UK) has also been used in wound healing trials . A study using this device also correlated the results taken from three acute punch biopsy wound healing studies and showed that these data were comparable to CD31 immunohistochemistry results .…”
Section: Proliferationmentioning
confidence: 99%
“…However, the sample size was low, which means that their results should be interpreted with caution. SIAscopy has also been compared with immunohistochemistry from the tissue biopsies in an acute wound healing model . The collagen, melanin and haemoglobin results taken from the device were compared to collagen I, collagen III, Masson Fontana and CD31 staining, which showed that the data correlated well.…”
Section: Remodellingmentioning
confidence: 99%